Sound velocity characteristics of unconsolidated sediment based on high-resolution sub-bottom profiles in Jinzhou Bay, Bohai Sea of China. (15th March 2021) - Wang, Fangqi; Ding, Jisheng; Tao, Changfei; Lin, Xubo
Abstract: Accurate inversion of sound velocity in a Holocene stratum and a Quaternary stratum was achieved based on rich high-resolution sub-bottom profiles and boreholes in the Jinzhou Bay, Bohai Sea of China. The average value of the sound velocity is 1540.2 m/s in the Holocene stratum and 1764.7 m/s in the Quaternary stratum. The fitting analysis shows that there is an obvious positive linear correlation between the sound velocity and the burial depth of the stratum, with a gradient of 4.5 s −1 . The method involving the solution of over-determined equations was innovatively put forward to explore the sound velocity characteristics of different types of sediments. The eigenvalues of the sound velocities of seven types of sediments and weathered rock in the study area are solved: the sound velocities of mud, muddy sand, muddy silty clay, muddy clay, silty clay, clay, silty sand, and strongly weathered rock are 1513.7 m/s, 1484.3 m/s, 1532.0 m/s, 1511.3 m/s, 1693.9 m/s, 1602.7 m/s, 1599.4 m/s, and 2137.7 m/s, respectively. And statistical analysis shows that the sound velocity of the sediment in the study area has obvious quadratic correlations with the void ratio and compressibility. Highlights: Based on sub-bottom profiles and boreholes datasets, this paper develops a method of acoustic inversion of seabed sediment. Innovatively establishing over-determined equations to solve sound velocities of different types of sediments. Findings can provide important reference values to the geophysical survey and the development of seabed geoacoustics.